2002
DOI: 10.1381/096089202321019576
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Serum Leptin to Clinical and Anthropometric Findings in Obese Patients

Abstract: In obese subjects multiple factors underlie the metabolic syndrome and therefore more than one mechanism may account for the clustering characteristics. In obese patients leptin loads only one factor, and therefore leptin does not appear to be a key feature in the metabolic syndrome. On the contrary, multiple correlation and factor analysis data give rise to the hypothesis that in obese patients, leptin may play a protective role against cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
3
6
0
3
Order By: Relevance
“…However, according to our results, it is difficult to state that in obese subjects total serum leptin is a cardiovascular risk factor because of its direct bivariate association with HDL‐cholesterol in women and its inverse association with the lipid atherogenic fractions: total cholesterol in men, the ratio total cholesterol‐to‐HDL‐cholesterol in women, and LDL‐cholesterol in both genders. This has been partially described by other authors suggesting a protector role for leptin in obese people (27, 28). Furthermore, multivariate analysis confirmed the direct association between leptin and HDL‐cholesterol.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, according to our results, it is difficult to state that in obese subjects total serum leptin is a cardiovascular risk factor because of its direct bivariate association with HDL‐cholesterol in women and its inverse association with the lipid atherogenic fractions: total cholesterol in men, the ratio total cholesterol‐to‐HDL‐cholesterol in women, and LDL‐cholesterol in both genders. This has been partially described by other authors suggesting a protector role for leptin in obese people (27, 28). Furthermore, multivariate analysis confirmed the direct association between leptin and HDL‐cholesterol.…”
Section: Discussionsupporting
confidence: 63%
“…A possible explanation for this phenomenon is that free and bound leptin have different correlations to altitude and a differential behavior on HDL‐cholesterol. Unfortunately, we measured only total leptin, and we can now only speculate about this, but Adami et al have proposed that some cardiovascular protection could be obtained from leptin merely because of the presence of a sufficient amount of fat mass (27), and this is equivalent to a high enough concentration of free leptin.…”
Section: Discussionmentioning
confidence: 95%
“…Research has directly linked increases in body fat to increased triglyceride and serum glucose levels in both monkeys [Kemnitz et al, 1989;Bodkin et al, 1993] and humans [Anderson et al, 1988;Adami et al, 2002;Huang et al, 2004]. These metabolic characteristics, along with increased leptin and insulin, constitute a means for measuring relative obesity.…”
Section: Discussionmentioning
confidence: 99%
“…1,[13][14] Multivariate analysis such as factor analysis of the MetS risk factors has identified important latent factors. Investigations of MetS through factor analysis have varied in terms of the number of risk factors considered and different studies have reported a group of factor domains [15][16][17][18][19][20][21][22] or a single (primary) MetS factor. [23][24][25][26][27][28][29] A number of clinical studies have been performed for attenuating the compound effect of MetS components.…”
mentioning
confidence: 99%